ETHNOPOLITICAL DYNAMICS AND THE TRANSFORMATION OF ISLAMIC RELIGIOUS EDUCATION CURRICULUM: A THEORETICAL FRAMEWORK FOR INCLUSIVE PEDAGOGY - Fitroh; Alhamuddin; Askin, Ikin (LPPM STAI Muhammadiyah Probolinggo, 2025)
This article aimed to explore the theoretical basis of etnopolitical influences on the transformation of the Islamic Religious Education curriculum, focusing on integrating multicultural awareness and deep learning approaches. The study used a comprehensive literature review and conceptual analysis to examine how ethnic identities and sociopolitical dynamics shaped curriculum reform in pluralistic societies. The findings showed that incorporating ethnopolitical perspectives into curriculum development fostered inclusive pedagogy that respected cultural diversity while promoting critical, reflective, and meaningful learning experiences. The framework highlighted the need for curricula that not only transmitted religious knowledge but also built social cohesion and character among diverse student populations. The study identified challenges in balancing local cultural identities with national unity and recommended flexible, context-sensitive educational policies and teacher training. Overall, this article contributed to understanding how ethnopolitics informed curriculum innovation, ensuring Islamic education remained relevant and responsive to societal complexities.